Manajemen Risiko Adventure Tourism Dalam Melakukan Kegiatan Paralayang di Nyang Nyang Paragliding - Liyandra, Adelia; Bhaskara, Gde Indra; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA, 2024)
Risk management in the context of adventure tourism is strategies taken to prevent the risk when doing highrisk tourism activities. One of the most dangerous adventure activities is paragliding. Paragliding is an adventure activity that uses a parachute to glide into the air from a high altitude. This research aims to find the risks of paragliding and risk management strategies. This research uses qualitative obtained through observation, interview, and documentation. Researchers used purposive sampling in selecting informants. The data collected was analyzed using qualitative descriptive analysis. The results of this study are firstly there are 3M (man, machine, media) that affect paragliding activity. If one of those three things don’t meet the requirements, there will be a risk of death, injuries, potential collision, etc. Secondly, this study uses the model of risk management practice in mountain adventure tourism (after British Mountaineering Council) which is adapted to the actions taken by Nyang Nyang Paragliding managers in risk management. Keywords: Risk Management, Adventure Tourism, Paragliding